A Faustian Foreign Policy from Woodrow Wilson to George W. Bush Dreams of Perfectibility - Hoff, Joan (Cambridge University Press, 2013)
Unkowningly, American colonists took the first step on the path to a Faustian foreign policy the moment they set out on their “errand into the wilderness” in the New World. Despite their constant jeremiads about sinfulness and “incessant and never successful cry for repentance, the Puritans launched themselves upon the process of Americanization.” Even though the Puritans initially expressed doubts about territorial expansion because of their fears of encountering the “profane,” later explorers, immigrants, homesteaders, and fur traders carried this Americanization process across the continent with largely the same unshakable and shared belief that their endeavor was blessed by God. In effect, they turned the jeremiad “doctrine of [God’s] vengeance into a promise of ultimate success, affirming the world, and despite the world, the inviolability of the colonial cause.” Americans came to believe that they would achieve their errand – and ultimately their dream of Manifest Destiny – because they represented a sanguine force for good